The Role of Human Resource Management in Addressing Unpaid Overtime Practices at PT Sai Apparel Industries, Grobongan, Central Java, and Its Implications for Employee Welfare - Harmen, Hilma; Gracia Manurung, Heva; Hawani, Saniah Lidiya; Gloria S. Sipahuta, Paskah; Agriyani, Siti (Jurnal Manajemen Bisnis Eka Prasetya, 2025)
The issue of unpaid overtime wages remains a significant labor challenge in Indonesia, particularly in the manufacturing sector. The case of PT Sai Apparel Industries in Grobogan, Central Java, highlights how discrepancies in work hour records and weak internal oversight lead to employees not receiving their rightful wages as mandated by Law No. 13 of 2003 on Manpower. This study employs a descriptive qualitative method with a literature review approach to analyze the role of Human Resource Management (HRM) in addressing unpaid overtime practices and preventing future violations. Findings indicate that non-compliance with labor regulations negatively impacts employee well-being, increases turnover rates, and damages corporate reputation. HRM plays a strategic role in ensuring compliance through technology-based work hour tracking, labor law training, regular audits, and transparent grievance mechanisms. By implementing these strategies, companies can mitigate legal risks, enhance employee welfare, and foster a fair and sustainable work environment.